Influence Of Parental Provision Of Academic Tools On Pupils’ Academic Achievement In Public Primary Schools In Gucha Sub-County, Kenya - Josephine Onsare,; Dr. George Ogochi, (IJRDO- Journal of Educational Research, 2020)
Education is a key factor to the development of any nation in the world. It has been the intension of the government that all KCPE candidates join secondary schools. Since 2003, the government has been providing funds to all public primary schools to promote access and education standards in all parts of the country. However, quite a number of public primary schools have been performing poorly in KCPE. In Gucha Sub-County, the average KCPE performance in 2016 was 246.4 marks. The purpose of this study was to assess the influence of home-school collaboration on pupils’ academic achievement in public primary schools in Gucha Sub-County, Kenya. The study was guided by the goal setting theory and the General system Theory. The study utilised mixed methods approach and concurrent triangulation design. The target population of study was 5213 respondents consisting of 828 teachers, 77 head teachers , 4231pupils and 77 Chairpersons’ of the School Management Committee. The sample size was 361 respondents. The sample comprised of 57 teachers, 6 head teachers, 292pupils and 6 Chairpersons’ of the School Management Committee using Morgan and Krejcie’s (1970) table to determine the sample size.. The study used questionnaire as research instruments. The instruments were piloted in 10 randomly selected secondary schools in the neighbouring Kitutu Chache Sub-County. The instruments validation exercise was done by the supervisors. A test- retest reliability technique was used to determine the reliability of the instruments where a coefficient of 0.76 was established. Descriptive statistics and   Inferential statistics were used to analyse data. Data was then presented through tables while bivariate analysis using Pearson Product Moment Correlation Coefficient to test if there was any relationship between teacher dynamics and student academic performance respectively. The study established that academic tools, parent-teacher communication frequency, parent involvement in school activities and parent monitoring positively and significantly influence pupils’ academic performance. The study recommends that Parents should provide academic tools to their children for them to perform well in their academics, to enhance academic performance of the pupils, parents and teachers should regularly communicate on issues of academics and how they can improve on the performance of the learners, Parents should actively be involved in school activities like discipline and school programmes as they enhance the performance of their children in academics and Parents should constantly monitor their children activities related to education as monitoring is the highest contributor to their children performance in academics.